Горячий снег: роман / Юрий Бондарев - Бондарев Юрий Васильевич (Великая победа, 2014)
Экземпляры: ф.6 (20231211) / Инвентарный номер: 4114zzz / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 74 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44